Классификация методов измерения вольт-амперных характеристик полупроводниковых приборов - Iermolenko, Ia. O. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
It is shown that computer systems for measuring current-voltage characteristics are very important for semiconductor devices production. The main criteria of efficiency of such systems are defined. It is shown that efficiency of such systems significantly depends on the methods for measuring current-voltage characteristics of semiconductor devices. The aim of this work is to analyse existing methods for measuring current-voltage characteristics of semiconductor devices and to create the classification of these methods in order to specify the most effective solutions in terms of defined criteria.To achieve this aim, the most common classifications of methods for measuring current-voltage characteristics of semiconductor devices and their main disadvantages are considered. Automated and manual, continuous, pulse, mixed, isothermal and isodynamic methods for measuring current-voltage characteristics are analysed. As a result of the analysis and generalization of existing methods the next classification criteria are defined: the level of automation, the form of measurement signals, the condition of semiconductor device during the measurements, and the use of mathematical processing of the measurement results. With the use of these criteria, the classification scheme of methods for measuring current-voltage characteristics of semiconductor devices is composed and the most effective methods are specified.